Design and implementation of high sampling rate and multichannel wireless recorder for EEG monitoring and SSVEP response detection - Li, Ruikai; Zhang, Yixing; Fan, Guangwei; Li, Ziteng; Li, Jun; Fan, Shiyong; Lou, Cunguang; Liu, Xiuling (Frontiers in Neuroscience, 2023)
The collection and process of human brain activity signals play an essential role in developing brain-computer interface (BCI) systems. A portable electroencephalogram (EEG) device has become an important tool for monitoring brain activity and diagnosing mental diseases. However, the miniaturization, portability, and scalability of EEG recorder are the current bottleneck in the research and application of BCI. For scalp EEG and other applications, the current study designs a 32-channel EEG recorder with a sampling rate up to 30 kHz and 16-bit accuracy, which can meet both the demands of scalp and intracranial EEG signal recording. A fully integrated electrophysiology microchip RHS2116 controlled by FPGA is employed to build the EEG recorder, and the design meets the requirements of high sampling rate, high transmission rate and channel extensive. The experimental results show that the EEG recorder provides a maximum 30 kHz sampling rate and 58 Mbps wireless transmission rate. Experiments were performed on scalp and intracranial EEG collection, an inflatable helmet with adjustable contact impedance was designed, and steady-state visual evoked potential (SSVEP) identification results demonstrate that the designed EEG collection system is simple and comfort, has high measurement performance and great potential for practical application in BCI systems.